The Ability of Student’s Spelling at SMA 8 Muaro Jambi - Ismiyati, Yanti; Yurni, Yurni; Myeli, Gustina Grace (JELT: Journal of English Language Teaching, 2024)
This study investigates the spelling abilities of twelfth-grade students at SMA 8 Muaro Jambi, Indonesia, with a specific focus on English nouns. Despite the early introduction of English in Indonesian schools, many students continue to struggle with spelling into their high school years. The research employs a quantitative descriptive approach, utilizing word identification tasks to assess students' spelling proficiency. A sample of students from class IPA 3 participated in a 30-item spelling test, which included both dictation and recognition tasks. The study reveals common spelling errors, including character omissions and substitutions with Indonesian equivalents, indicating a lack of familiarity with English spelling patterns and an over-reliance on phonetic spelling based on the native language. The findings highlight the complexity of spelling as a fundamental aspect of language proficiency, encompassing phonological, visual, morphological, and etymological knowledge. This research contributes to the field of English language education in Indonesia by providing insights into spelling challenges faced by high school students and their implications for overall language proficiency. The results can inform the development of more targeted and effective spelling instruction methods, addressing the persistent gaps in English language acquisition among Indonesian learners.